Disentangling the factors driving users' continuance intention towards social media: A configurational perspective. (August 2018) - Li, Hongxiu; Li, Lirui; Gan, Chunmei; Liu, Yong; Tan, Chee-Wee; Deng, Zhonghua
Abstract: Building on perceived value theory, this study employs fuzzy set Qualitative Comparative Analysis (fsQCA) to derive configurational models that embody causal conditions for predicting users' continuance intention towards social media. From reviewing extant literature, we advanced four value dimensions to be gained from social media usage, namely hedonic value (enjoyment), information value (information documentation and information sharing), media value (media appeal), and social value (social interaction), which are measured via a survey questionnaire. Our findings reveal seven distinct configurations of causal conditions for inducing continuance intention towards social media among Chinese users. Particularly, the frequency of social media usage combined with perceptions of enjoyment were found to be core conditions reinforcing users' continuance intention towards social media. In turn, the existence of multiple configurations implies that social media service providers could concurrently pursue differentiated strategies for retaining users. Highlights: The relationships between the motivators and IS user behavior might be asymmetric. Seven different configurations bring the same outcome of continuance intention. Use frequency and perceived enjoyment are the core conditions. Different strategies should be taken to retain social media customer.